2007
DOI: 10.1073/pnas.0709802104
|View full text |Cite
|
Sign up to set email alerts
|

B7-H3 and B7x are highly expressed in human prostate cancer and associated with disease spread and poor outcome

Abstract: B7-H3 and B7x are recently discovered members of the B7-CD28 family thought to dampen peripheral immune responses via negative costimulation. We evaluated their potential expression in human prostate cancer using a large cohort of patients with 7 years of follow-up. We identified 823 patients with tissue available treated with radical prostatectomy between 1985 and 2003. Immunohistochemistry was performed on tissue microarray sections using anti-B7-H3 and -B7x. The percentage and intensity of immunoreactivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

28
337
2
4

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 345 publications
(371 citation statements)
references
References 41 publications
28
337
2
4
Order By: Relevance
“…These data suggested that tumour-associated B7-H3 expression might promote immune response as a positive regulator. By sharp contrast, the negative role of B7-H3 expression has been reported in lung and prostate cancers Roth et al, 2007;Zang et al, 2007). In nonsmall-cell lung cancer, B7-H3 expression was inversely correlated with the number of tumour-infiltrating lymphocytes, and a high B7-H3 expression was more common in patients with lymph node metastasis .…”
mentioning
confidence: 68%
See 1 more Smart Citation
“…These data suggested that tumour-associated B7-H3 expression might promote immune response as a positive regulator. By sharp contrast, the negative role of B7-H3 expression has been reported in lung and prostate cancers Roth et al, 2007;Zang et al, 2007). In nonsmall-cell lung cancer, B7-H3 expression was inversely correlated with the number of tumour-infiltrating lymphocytes, and a high B7-H3 expression was more common in patients with lymph node metastasis .…”
mentioning
confidence: 68%
“…B7-H3 expression has been identified in several tumour cell lines and in actual human tumour specimens, including gastric cancer, non-small-cell lung cancer, and prostate cancer Wu et al, 2006;Roth et al, 2007;Zang et al, 2007). Several murine studies have shown that introduction of B7-H3 in tumour cells and tissues by various methods activates tumour-specific immunocompetent cells and promotes anti-tumour response, thereby leading to rapid tumour regression, reduction of metastasis, and prolongation of animal survival (Sun et al, 2003;Luo et al, 2004Luo et al, , 2006Lupu et al, 2006Lupu et al, , 2007.…”
mentioning
confidence: 99%
“…In contrast to our observations, a previous study reported that high PD-L1 expression in tumors was associated with poor prognosis and adverse clinicopathological findings in GC [15,16]; various other tumors with PD-L1(?) expression have also been reported to have poor prognoses in some studies [23,[28][29][30]. However, the prognostic impact of PD-L1 expression in patients with cancer remains controversial to date.…”
Section: Discussionmentioning
confidence: 99%
“…Key genes for the regulation of embryonic organogenesis (Hoxa5, Hoxa9, Foxc1 and Foxf2) and the commitment of immature cells to multiple lineages (Pparg, Cebpa, Plxnd1, Egfl7, Mgp, Plxdc2, Ebf1 and Tcf3) were expressed at higher levels in AO cells than in AX cells, suggesting that AO cells have characteristics of immature mesenchymal cells (Wang and Reed, 1993;Luo et al, 1997;Wu et al, 1999;Rosen et al, 2000;Parker et al, 2004;Torres-Vazquez et al, 2004;Miller et al, 2007;Cole et al, 2008). The profile of AX cells, on the other hand, was indicative of both cells that are committed to the osteocyte lineage (Dlx3, Sp7, Dkk1, Ostn and Bmp3) and cells that are inclined to tumorigenesis in vivo (Cd276, Ptgs2, Vegfa, Epha2, Frzb and Sfrp1) (Kim et al, 1993;Daluiski et al, 2001;Dannenberg et al, 2001;Thomas et al, 2003;Lee et al, 2004 Zang et al, 2007;Brantley-Sieders et al, 2008;Engin et al, 2008;Li et al, 2008).…”
Section: Ao and Ax Cells Differ In Their Gene Expression Profilesmentioning
confidence: 97%